Проблеми фінансової політики Російської імперії в роки Першої світової війни в науковій спадщині М.І.Тугана-Барановського - Орлик, С.В. (Український історичний журнал, 2017)
Досліджується наукова діяльність М.І.Тугана-Барановського, спрямована на
пошук оптимальної фінансово-економічної політики в умовах спричиненого
війною кризового економічного становища Російської імперії. Розглянуто теоретичні
погляди фахівця щодо монетарної економіки та особливості їх реалізації
у процесі створення національної грошової системи періоду Центральної
Ради та Директорії. Зроблено висновок, що публікації М.І.Тугана-Барановського
стали важливим джерелом для сучасних дослідників процесів, які відбувалися у
фінансово-економічній сфері Російської імперії часів Першої світової війни. The article discloses the viewpoints of the well-known Russian and Ukrainian scholar
M.I.Tuhan-Baranovs’kyi concerning the financial policy of the government of the
Russian Empire during World War I. The scholar’s scientific and public activities directed
to the search of the most advantageous financial and economic policy in the conditions
of economic crisis in the Russian Empire conditioned by the war were studied.
While analyzing the works of M.I.Tuhan-Baranovs’kyi it was possible to distinguish
considerable factual materials concerning economic and financial situation in the
Russian Empire during World War I. Theoretical viewpoints in relation to the monetary
economy and the peculiarities of their realization in the process of creation of the monetary
system of the Ukrainian state during Central Council and Directorate were considered.
It was concluded that the publications of M.I.Tuhan-Baranovs’kyi are the important
source for contemporary researchers of the historical processes that took place
in the financial and economic sphere of the Russian Empire during the World War I.